Assessment of success of the Ponseti method of clubfoot management in sub-Saharan Africa: a systematic review - Smythe, T; Mudariki, D; Kuper, H; Lavy, C; Foster, A (BioMed Central, 2017)
Background Clubfoot is one of the most common congenital deformities affecting mobility. It leads to pain and disability if untreated. The Ponseti method is widely used for the correction of clubfoot. There is variation in how the result of clubfoot management is measured and reported. This review aims to determine and evaluate how success with the Ponseti method is reported in sub-Saharan Africa. Methods Five databases were examined in August 2017 for studies that met the inclusion criteria of: (1) evaluation of the effect of clubfoot management; (2) use of the Ponseti method; (3) original study undertaken in sub-Saharan Africa; (4) published between 2000 and 2017. We used the PRISMA statement to report the scope of studies. The included studies were categorised according to a hierarchy of study methodologies and a 27-item quality measure identified methodological strengths and weaknesses. The definition of success was based on the primary outcome reported. Results Seventy-seven articles were identified by the search. Twenty-two articles met the inclusion criteria, of which 14 (64%) reported a primary outcome. Outcomes were predominantly reported though case series and the quality of evidence was low. Clinical assessment was the most commonly reported outcome measure and few studies reported long-term outcome. The literature available to assess success of clubfoot management is characterised by a lack of standardisation of outcomes, with different measures reporting success in 68% to 98% of cases. Conclusion We found variation in the criteria used to define success resulting in a wide range of results. There is need for an agreed definition of good outcome (successful management) following both the correction and the bracing phases of the Ponseti method to establish standards to monitor and evaluate service delivery.